El desarrollo psicomotriz de los 3 a 6 años, a partir de la guabina chiquinquireña en la fundación muzo (Memorias Sifored - Encuentros Educación UAN, 2023)
In the present presentation “The psychomotor development of 3 to 6 years from the guabina chiquinquireña of the Muzo foundation” we will talk about the experience of the (EAPEAT), carried out by third semester students of the Antonio Nariño University, and how This has helped the understanding of psychomotor development in the training of the boys and girls of Muzo
Keywords: Educational strategies; cultural organization; infancy; dance